Apakah Kepercayaan Memediasi Pengaruh Reputasi Bank dan Religiusitas Terhadap Purchase Intention? - Hanifah Jasin; Siti Mujiatun; Muis Fauzi Rambe; Rahmad Bahagia Siregar (JURNAL ILMIAH MANAJEMEN & BISNIS, 2021)
The purpose of this research is to study the factors that influence trust and purchase intention on Islamic Bank Products in Medan City and produce models for measuring trust and purchase intention on Islamic Bank products in Medan City. In this study the population is unknown, therefore a representative sample with non-probability sampling technique is needed and the method used is purposive sampling. In this study, the number of indicators is 21, so by using ten times the indicator calculation, the required sample size is 170 people. Data collection was carried out using observations, questionnaires and documentation studies. Data analysis in this study was carried out by using the Structural Equation Model (SEM). The results showed that there was a positive and significant influence on Bank Reputation on Trust, There was a positive and significant influence of Religiosity on Trust, there was a positive and significant influence on Bank Reputation on Purchase Intention, there was a positive and significant influence on Religiosity on Purchase Intention, there was a positive and significant influence. trust in Purchase intention. Trust can positively mediate the effect of Bank Reputation on Purchase Intention and Trust can positively mediate the influence of Religiosity on Purchase Intention.